Korosi Retak Tegang pada Pipa Superheater Ketel Uap yang Baru Dibangun [Stress Corrosion Cracking of Cage Superheater Tubes of a Newly Built Boiler] - Dewa Nyoman Adnyana (Metalurgi, 2017)
A number of cage superheater tubes of a newly built steam boiler have been leaking during boiler’s first start-up commissioning. Leaking occurred when the boiler had just reached a pressure of 23.7 barg and temperature 4050 C from the intended operating pressure of 53 barg and temperature of 4850C. Type of failure and factors that may have caused the leakage of the cage superheater tube are discussed in this paper. The metallurgical assessment was conducted by preparing a number of specimens from the as received leaked cage superheater tube. Various laboratory examinations were performed including macroscopic examination, chemical composition analysis, metallographic examination, hardness test and SEM (scanning electron microscopy) examination equipped with EDS (energy dispersive spectroscopy) analysis. Results of the metallurgical assessment obtained show that the leaked cage superheater tubes have been experiencing stress-corrosion cracking (SCC) caused by the combined effect of corrosion and tensile stress. The corrosion agent that may have been responsible for the occurrence of SCC in the tube was mostly due to caustic sodium (Na) and other elements in a lesser extent such as Ca, Cl, S and P.AbstrakSejumlah pipa penukar panas lanjut pada sebuah ketel uap yang baru dibangun diketemukan bocor selama operasi komisioning yang pertama. Kebocoran terjadi ketika ketel uap baru saja mencapai tekanan 23,7 barg dan temperatur 405 °C dari tekanan dan temperatur operasi yang direncanakan yaitu 53 barg dan 485 °C. Dalam makalah ini dibahas jenis kerusakan dan faktor-faktor yang kemungkinan telah menyebabkan terjadinya kebocoran pada pipa penukar panas lanjut tersebut. Penelitian/pengujian metalurgi telah dilakukan dengan mempersiapkan sejumlah benda uji yang diperoleh dari salah satu potongan pipa yang bocor tersebut. Berbagai pengujian laboratorium telah dilakukan meliputi: uji makro, analisa komposisi kimia, uji metalografi, uji kekerasan dan uji SEM (scanning electron microscopy) yang dilengkapi dengan analisis EDS (energy dispersive spectroscopy). Hasil penelitian/pengujian metalurgi yang diperoleh menunjukkan bahwa pipa penukar panas lanjut yang bocor tersebut telah mengalami retak korosi tegangan yang disebabkan oleh efek kombinasi antara korosi dan tegangan tarik. Unsur korosif yang kemungkinan dapat menimbulkan terjadinya retak korosi tegangan pada pipa penukar panas lanjut adalah kaustik sodium (Na) dan elemen-elemen lainnya pada tingkatan yang relatif rendah seperti Ca, Cl, S dan P.